2011
DOI: 10.1177/0004865811419067
|View full text |Cite
|
Sign up to set email alerts
|

Deliberating about terrorism: Prejudice and jury verdicts in a mock terrorism trial

Abstract: Juries in many Western countries are being asked to make decisions about defendants charged with terrorist-related offences, in situations where heightened anxieties and hostility to outgroups may make a fair trial difficult. What impact can deliberation have in addressing any such prejudice? This study estimates the impact of several forms of prejudice on juror verdicts in a mock terrorism trial. The study provides a more realistic setting than most previous studies, with an authentic heritage courtroom, actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…There is a large body of social-psychological literature on how gender, race, social class, bias, and prior attitudes may impact jury decision-making (see Devine 2012 for a thorough review). This research suggests that while background characteristics and attitudes can impact decision-making, in some cases deliberation seems to reduce prior biases (Tait 2011, Devine 2012). This analysis does not seek to underplay what jurors bring with them to the deliberation table in terms of status characteristics and attitudes.…”
Section: Methodology and Analytic Approachmentioning
confidence: 84%
See 1 more Smart Citation
“…There is a large body of social-psychological literature on how gender, race, social class, bias, and prior attitudes may impact jury decision-making (see Devine 2012 for a thorough review). This research suggests that while background characteristics and attitudes can impact decision-making, in some cases deliberation seems to reduce prior biases (Tait 2011, Devine 2012). This analysis does not seek to underplay what jurors bring with them to the deliberation table in terms of status characteristics and attitudes.…”
Section: Methodology and Analytic Approachmentioning
confidence: 84%
“…This paper examines a deliberation from a single jury who received visual evidence, expert testimony, and judicial instructions. It does not present the results of the larger experiment (see Tait 2011 andGoodman-Delahunty 2016). The exploratory nature of the investigation and the unique richness of the video data make an analysis of a single case suitable.…”
Section: Methodology and Analytic Approachmentioning
confidence: 99%
“…Given the absence of a consistent theme in the data gathered concerning this issue, little can be concluded about the impact of the deliberation process with respect to pre-trial publicity. Tait’s 2010 empirical work concerning juror bias in terrorism trials notes that the results supported the hypothesis that deliberation may reduce conviction levels (Tait, 2011: 397). However, the evidence has not yet reached a stage where a conclusion could be drawn with confidence in relation to the impact of deliberations on the prejudicial impact of pre-trial publicity.…”
Section: Lessons From the Psycho-legal Scholarshipmentioning
confidence: 95%
“…Although individual verdict preferences have been shown to be a consistent predictor of group outcomes (Davis, 1973;Devine et al, 2001), it is possible that the results would vary if a group deliberation component was used (see Salerno & Diamond, 2010; see also Garcia et al, 2021). For example, prior studies have suggested that deliberations may help reduce the impact of certain sources of bias, such as bias from exposure to inadmissible evidence (London & Nunez, 2000) or prejudice related to terrorism (Tait, 2011). Additional research is therefore needed to explore whether the effects 93 observed in this study would be consistent, amplified or reduced with the inclusion of deliberations.…”
mentioning
confidence: 99%